The Macro-Economics of Crypto-Currencies: The Role of Private Moneys in Monetary Policy - Eli Noam (International Telecommunications Society (ITS), 2021)
Cryptocurrencies provide an important dimension of innovation to the evolution of the exchange medium we call money. There are now over 4,000 such currencies, and their potential and volume is growing. The impact of such currencies for money laundering, law enforcement, and banking supervision have been extensively discussed on the transaction level. But this is the "micro" level of analysis. What has been rare is a "macro" level discussion of the impact on the monetary system of a country. Central banks, which are institutions tasked with providing monetary stability, will see their problems rise while the power of their traditional tools to control money supply and interest rates - such as reserve requirements and the discount rates - is declining. But the new digital technologies - such as distributed ledgers - and new approaches provide regulatory bodies also with new and potentially powerful tools. The task for central banks and policy makers is to create new approaches to use, regulate, and incent them in shaping the macro-economic path of their economy. The paper will propose several of these approaches. This is of particular importance in an economic recovery post coronavirus. In the process, central banks will also, predictably, issue their own digital currencies, and a tiny number of those will become global super-currencies. This will create a new type of issues.
Keywords: 330